Pediatric Lymphedema: Study of 180 Patients Referred to a Tertiary Lymphedema Clinic. Issue 5 (September 2022) - Colmant, Caroline; Turpin, Sophie; Lambert, Raymond; Wong, Nicole; Ondrejchak, Sandra; Lapointe, Chantal; Powell, Julie; Dubois, Josée; McCuaig, Catherine
Background: Lymphedema is due to dysfunction of the lymphatic system. It can be primary or secondary. Pediatric lymphedema is more often primary and is a chronic disease with a heavy burden on quality of life. Methods: Medical records of patients under 18 years of age referred between 1996 and 2021 to the specialized lymphedema clinic at the Sainte-Justine University Hospital Center were reviewed. Demographic data, sex, age at presentation, location of the lymphedema, clinical features, genetic testing, symptoms, complications, investigations, and treatment were collected. Results: Of 180 referred patients, lymphedema was confirmed in 151, and 137 were primary lymphedema. Median age of apparition of primary lymphedema was 7.00 years and was significantly lower in boys than in girls. Primary congenital lymphedema was more frequent in boys (51.0%, 27.3% in girls, P = .007), and onset of primary lymphedema during adolescence was more frequent in girls (53.4%, 25.0% in boys, P = .001). Lower limbs were the most impacted (88.3%). Sixty patients had genetic testing, and 38 (63.3%) of them were discovered to have a pertinent genetic mutation. The most common mutated gene was the FLT4 gene (in 9 patients). Seven patients (5.1%) had associated extensive/central lymphatic malformation and 24 (17.6%) had a polymalformative syndrome/syndromic lymphedema. Conclusions: Pediatric lymphedema is more frequent in girls, usually involves lower limb, and is most often sporadic, but often associated with a genetic mutation, and genetic testing should be performed.